Adenosine Metabolism, Immunity and Joint Health - Hasko, George (Biochem Pharmacol, 2018)
The purine nucleoside adenosine is a present in most body fluids where it regulates a wide variety of physiologic and pharmacologic processes. Adenosine mediates its effects through activating 4 G protein-coupled receptors expressed on the cell membrane: A1, A2A, A2B, and A3. The adenosine receptors are widely distributed in the body, and tissues with high expression include immune tissues, cartilage, bone, heart, and brain. Here we review the source and metabolism of adenosine and the role of adenosine in regulating immunity and cartilage biology.